Ivan KARP et Steven D. LAVINE, éditeurs, Exhibiting Cultures: The Poetics and Politics of Museum Display, Washington et Londres, Smithsonian Institution Press, publié en collaboration avec l’American Association of Museums, 1991, 468 pages, illustré - Lawson, Barbara (Culture, 1993)
Pointe-à-Callière, a young Museum rising above the site of the founding of Montréal, first opened its doors on May 17, 1992. Its permanent exhibition of more than 4,000 m allows visitors to examine architectural remuants, archaeological artifacts and an 18th-century heritage building. The Museum's goal is to bring the history of Montréal alive and to illustrateit in an entertaining way. Visitors roam among authentic remuants testifying to the successive inhabitants of this site: Indians, French, British, North Americans and Quebeckers. A tour of the Museum, alone, as a family or with an interpreter-guide, is a chance to discover Montréal through its archaeological heritage. It also leads us to reflect on our own role in the way the past is preserved. Finally, it makes us think about how the traces we in turn leave behind will be tomorrow's heritage for the generations to come.